2017
DOI: 10.1051/matecconf/201712502003
|View full text |Cite
|
Sign up to set email alerts
|

Lean Production Practices to Enhance Organisational Performance

Abstract: Abstract. Service sector organisations are constantly overcoming the challenges facing the overproduction and waste reduction within their environments. Industries are also becoming very competitive thus forcing them to seek suitable production organisation strategies with the aim towards enhancing their competitiveness and efficiency. The aim of this research study is to investigate the impact of lean production practices on the performance of service based businesses through the case study of a local baked g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 23 publications
(20 reference statements)
1
9
0
Order By: Relevance
“…Specifically, the results showed that LM practices are effective for operational performance improvement in both low IC and high IC industries. The study is also supported by Knudtzon (2018), Pozo et al (2018), Khanchanapong et al (2014), Belekoukias et al (2014), Birkie and Trucco (2016), Dal Pont et al (2008), Furlan et al (2011), Taj and Morosan (2011), Hallgren and Olhager (2009), Shah et al (2017) and Chavez et al (2013) that show that the implementation of LM practices improves operational performance.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Specifically, the results showed that LM practices are effective for operational performance improvement in both low IC and high IC industries. The study is also supported by Knudtzon (2018), Pozo et al (2018), Khanchanapong et al (2014), Belekoukias et al (2014), Birkie and Trucco (2016), Dal Pont et al (2008), Furlan et al (2011), Taj and Morosan (2011), Hallgren and Olhager (2009), Shah et al (2017) and Chavez et al (2013) that show that the implementation of LM practices improves operational performance.…”
Section: Discussionsupporting
confidence: 61%
“…There seems to be an impression that variables such as quality, cost, speed, flexibility and dependability are popular measures of operational performance (Knudtzon, 2018; Pozo et al , 2018; Khanchanapong et al , 2014; Belekoukias et al , 2014; Birkie and Trucco, 2016; Dal Pont et al , 2008; Furlan et al , 2011; Taj and Morosan, 2011; Hallgren and Olhager, 2009; Shah et al , 2017; Chavez et al , 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…(Shah et al, 2017) As shown from Table XIII, it is clear that the mean average of 3.61 (max 5.0) and that of 72.2% was high. Many of the respondents highlighted that the implementation of lean production practices impact has been the highest on the profitability performance of the organisation at 4.13.…”
Section: Lean Production Practices Adoption In Company Xmentioning
confidence: 89%
“…(Shah et al, 2017) The key question analysed within this research focused towards 'what waste do lean production practices eradicates within your organisation'. The results from this analysis provided a mean of 86.6% from the respondents that indicated the contribution of this criterion relatively high, and 40% of were 'strongly agree', 53.32% were 'agree' and 33.3% were 'undecided'.…”
Section: Vsmmentioning
confidence: 99%
See 1 more Smart Citation